Sensitivity analysis of optimization models for two adjacent intersections with correlated short left-turn lanes - Yao, Ronghan (Transport, 2013)
The correlated short left-turn lanes sometimes exist on the common section between two adjacent intersections. These short lanes can reduce the approach capacity and impact on each other. According to operational research, three kinds of multi-objective optimization models are put forward in order to reasonably allocate the time-space resources of two intersections. Since the solutions to these models depend on the concrete forms of their objective functions, six feasible objective functions and the corresponding solution method are proposed. Next, the sensitivity of the optimization results to the parameters (minimum and maximum cycle lengths) is emphatically analyzed and compared. Moreover, to testify the effects of these models on traffic flow operations, three typical optimization scenarios are simulated together with the existing one. The models and methods are illustrated via the 2010 field data from the city of Dalian, China. Also, the better models and their suitable parameter values or ranges are recommended. Finally, the application procedure of the recommended models is given in actual engineering practice. First Published Online: 11 Oct 2013